Parties eaudiobook - Nascosta, C.M (Monster Bait Romance, 2022)
Several months after a girls' trip, elves Lurielle, Ris, and Silva are still affected by their experiences at the resort and the orcs they met there. Lurielle discovers that being in a multi-species relationship presents its own unique challenges: meeting Khash's family, introducing him to hers, and facing the harsh realities that lie ahead if they stay together. A lifetime together or a lifetime apart—she must decide if she can bear all that the future holds. When Ris returns to the resort, an unexpected encounter with a slightly familiar face upends this elf's desire to be a free as the wind. Ainsley is simultaneously everything and nothing that she's looking for—smart and sexy and completely unattached, and happy to stay that way . . . but how long can they keep things casual? Silva struggles juggling her two halves: Daytime Silva, crushed beneath the expectations of her family and Elvish society, and Silva of the Nighttime, unfettered and free, seeing Tate in secret. She must make a choice—will she follow the carefully mapped life of privilege her family has planned for her or throw it all away to follow her heart, for a man with his own heart full of secrets. Contains mature themes.